2013
DOI: 10.1007/978-3-319-03524-6_28
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Dynamical Structures in Artificial Brains: An Analysis of Boolean Network Controlled Robots

Abstract: Abstract. Automatic techniques for the design of artificial computational systems, such as control programs for robots, are currently achieving increasing attention within the AI community. A prominent case is the design of artificial neural network systems by means of search techniques, such as genetic algorithms. Frequently, the search calibrates not only the system parameters, but also its structure. This procedure has the advantage of reducing the bias introduced by the designer and makes it possible to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…The automatic design of BNs matching some target properties of biological cells, such as the distance between attractors or the capability of producing attractor landscapes with specific characteristics resembling differentiation trees, is the subject of more recent works [44][45][46]. Finally, it is worth mentioning that evolutionary algorithms and stochastic local search techniques in general have been also applied to design BNs which are capable of controlling robots [47,48], and the structural and dynamical properties of these BNs have been studied as well [49][50][51].…”
Section: Evolving Boolean Networkmentioning
confidence: 99%
“…The automatic design of BNs matching some target properties of biological cells, such as the distance between attractors or the capability of producing attractor landscapes with specific characteristics resembling differentiation trees, is the subject of more recent works [44][45][46]. Finally, it is worth mentioning that evolutionary algorithms and stochastic local search techniques in general have been also applied to design BNs which are capable of controlling robots [47,48], and the structural and dynamical properties of these BNs have been studied as well [49][50][51].…”
Section: Evolving Boolean Networkmentioning
confidence: 99%
“…Apart from few preliminary investigations (Roli et al, 2013(Roli et al, , 2015(Roli et al, , 2018, there is still much room for application of information-theoretic and complexity measures in the analysis of robot behavior. Besides the use of such metrics during the design process (e.g., to assessing the complexity of the swarm or the individual robots), we envisage a real-world scenario in which the complexity level of a robot swarm is monitored in order to detect specific phases of its behavior (e.g., when a decision has to be collectively taken) and possible failures-e.g., when a large discrepancy between the expected and actual complexity of the swarm is observed it might be the case that some malfunctioning dynamics is taking place.…”
Section: Open Questions and Opportunities For Future Researchmentioning
confidence: 99%
“…Along this line are the experiments in Boolean network robotics [16][17][18][19]. A BN is a discrete-time, discrete-state dynamical system whose state is an N-tuple in 0, 1 N , (x 1 , … , x N ).…”
Section: Attractors In Robotics Behaviormentioning
confidence: 99%
“…The algorithm employs as learning feedback a measure of the performance of the BN-controlled robot (in the following, BN-robot) on the task to perform, such as in evolutionary robotics [28]. For example, it was shown that a BN-robot can learn a composite mission, in which the first task is to perform phototaxis; then, after a sharp sound is perceived, the robot performs anti-phototaxis [16][17][18][19]. A dynamical systems' analysis shows that the behavior of the robot is mainly composed of three attractors: in the first the robot steadily rotates and in the second the robot goes straight.…”
Section: Attractors In Robotics Behaviormentioning
confidence: 99%
See 1 more Smart Citation